Kebijakan Penanggulangan Demam Berdarah Dengue (DBD) pada Berbagai Daerah di Indonesia - Rapitos siddiq; Aldri Aldri Frinaldi2; Rembrandt Rembrandt; Dasman Lanin; Genius Umar (Jurnal Sehat Mandiri, 2023)
The environment and behavior play an important role in the occurrence of health problems or diseases, such as Dengue Hemorrhagic Fever (DHF). DHF problems always occur from year to year, especially the number of cases, both globally and nationally and even locally. In Indonesia each region has different policies- in addressing DHF problems in their regions. This paper aims to describe several local government policies in dealing with DHF problems in several regions based on research results published in several journals. This research is in the nature of a review or article review. The results of the research reviewed in this article are 6 (six) articles, namely the range of 2018-2022. The aspects that are looked at are the title, author, year, objectives, methods, results and conclusions. The results of the study found that most local governments have different policies in tackling DHF, but with the aim the same thing, namely reducing DHF cases and preventing extraordinary events (KLB), such as by community empowerment, field action strategies and utilization of local wisdom. The conclusion is that regional policies in tackling DHF from 2018 to 2022 are able to reduce or control the incidence of DHF. To overcome unresolved problems related to behavior, it is better to use the Emotional Demonstration (Emo Demo) approach.